A corpus-driven analysis of Taylor Swift's song lyrics / Faruq Ahmad Kendong, Afifah Sakinah Daud and Siti Aeisha Joharry - Ahmad Kendong, Faruq Ahmad Kendong; Daud, Afifah Sakinah; Joharry, Siti Aeisha (Universiti Teknologi MARA, 2023)
Taylor Swift is widely recognized for her song writing skills, known for crafting relatable lyrics, catchy tunes, and personal storytelling that draws from her experiences and emotions. This exploratory study aims to explore the language used in Taylor Swift's song lyrics by analysing the language features, its collocations and the most used lexical bundles. A specialised corpus, the Taylor Swift Corpus (TSC), was compiled with a total of 189 song lyrics from 10 Taylor Swift albums, from her debut album - Taylor Swift (2004) to the latest release - Midnights (2022). TSC consists of song lyrics of different genres, including country, country rock, pop, country pop, folk and folk pop. #LancsBox 6.0 software was utilised for generating the statistics of the corpus, where the results were analysed further in order to fulfil the proposed research objectives in this research. Various corpus analyses were carried out including frequency analysis, collocational patterns analysis and examining the concordance lines. Findings revealed Taylor Swift's writing styles that are personalised in nature through use of the personal pronouns 'I' and 'you', followed by salient references to 'time' and her reflections on events via the cognitive verb 'know'. Future studies could investigate other properties of the artist's writing such as metaphorical or figurative use of language.